Elevating Urban Living: A Comprehensive Exploration of Smart and Happy Cities in India - Prasad, Amit (Journal of Advanced Research in Economics and Business Management, 2023)
This comprehensive review explores the dynamic interplay between the concepts of smart cities and happy cities within the unique landscape of urban development in India. The Government of India’s ambitious initiative, launched in 2015, aimed to transform 100 cities into smart cities, with an additional 500 cities slated for transformation in subsequent phases. This monumental undertaking, backed by a substantial financial commitment, underscores the paradigm shift towards technologically advanced urban spaces. Furthermore, the review delves into the emerging concept of a happy city, contextualizing it within the broader urban development narrative. The distinguishing factor lies in the emphasis on emotional infrastructure as the cornerstone of a city’s happiness. The intricate interplay between cultural practices, security measures, environmental consciousness, and collaborative community engagement is unraveled as essential components of a happy city. In essence, this review provides a nuanced understanding of the simultaneous evolution of smart cities and happy cities in India, presenting a balanced perspective on the convergence of technological progress and emotional well-being in the contemporary urban landscape. The discussion opens avenues for further research and policy considerations, highlighting the imperative of harmonizing technology-driven urbanization with the cultivation of emotionally enriched urban spaces for a more holistic and sustainable future.